Final answer to the problem
Step-by-step Solution
How should I solve this problem?
- Choose an option
- Find the derivative using the definition
- Find the derivative using the product rule
- Find the derivative using the quotient rule
- Find the derivative using logarithmic differentiation
- Find the derivative
- Integrate by partial fractions
- Product of Binomials with Common Term
- FOIL Method
- Integrate by substitution
- Load more...
Apply the product rule for differentiation: $(f\cdot g)'=f'\cdot g+f\cdot g'$, where $f=x^x$ and $g=\left(6x-3\right)^2\left(2x^2+8\right)^5$
Learn how to solve differential calculus problems step by step online.
$\frac{d}{dx}\left(x^x\right)\left(6x-3\right)^2\left(2x^2+8\right)^5+x^x\frac{d}{dx}\left(\left(6x-3\right)^2\left(2x^2+8\right)^5\right)$
Learn how to solve differential calculus problems step by step online. Find the derivative of x^x(6x-3)^2(2x^2+8)^5. Apply the product rule for differentiation: (f\cdot g)'=f'\cdot g+f\cdot g', where f=x^x and g=\left(6x-3\right)^2\left(2x^2+8\right)^5. Apply the product rule for differentiation: (f\cdot g)'=f'\cdot g+f\cdot g', where f=\left(6x-3\right)^2 and g=\left(2x^2+8\right)^5. The power rule for differentiation states that if n is a real number and f(x) = x^n, then f'(x) = nx^{n-1}. The power rule for differentiation states that if n is a real number and f(x) = x^n, then f'(x) = nx^{n-1}.